Interferon Nebulation in COVID-19 Patients - Rositianti, Rositianti; Muhammad Husain Haekal (Jurnal Keperawatan Silampari, 2025)
This study aims to see how effective interferon nebulization therapy is in COVID-19 patients. The method used is rapid review. The results of the study showed that rSIFN-co therapy has advantages, namely the duration of faster clinical improvement, the time for negative conversion of viral nucleic acid on mechanical ventilation is also shorter. While interferon-alpha therapy itself, because it still uses traditional principles, clinical improvement that occurs is a little slow. Conclusion, the use of interferon-alpha is less effective for the treatment of COVID-19 than the use of rSIFN-co therapy.   Keywords: COVID-19, Interferon, Nebulization